Postawy młodzieży wobec reklamy ambientowej: Attitudes of the young towards ambient advertising - Pudło, Kinga; Wyrwisz, Joanna (Management and Administration Journal, 2021)
The aim of this study was to present the possibility and conditions of using ambient advertising. The essence and the characteristics of the ambient media are described in the paper. The most important parts of this article are the results and analysis of research concerning attitudes of the young in view of this unconventional form of marketing communication.